Pulmonary hypertension associated with left heart disease: Updated Recommendations of the Cologne Consensus Conference 2018. (1st December 2018) - Rosenkranz, Stephan; Lang, Irene M.; Blindt, Rüdiger; Bonderman, Diana; Bruch, Leonhard; Diller, Gerhard P.; Felgendreher, Ralf; Gerges, Christian; Hohenforst-Schmidt, Wolfgang; Holt, Stephan; Jung, Christian; Kindermann, Ingrid; et al.
Abstract: In the summer of 2016, delegates from the German Society of Cardiology (DGK), the German Respiratory Society (DGP), and the German Society of Pediatric Cardiology (DGPK) met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary hypertension (PH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines, aiming at their practical implementation, considering country-specific issues, and including new evidence, where available. To this end, a number of working groups was initiated, one of which was specifically dedicated to PH associated with left heart disease. In this context, the European Guidelines point out that the drugs currently approved to treat patients with PAH (prostanoids, endothelin receptor antagonists, phosphodiesterase type 5 inhibitors, sGC stimulators) have not sufficiently been investigated in other forms of PH. However, despite the lack of respective efficacy data, an uncritical use of targeted PAH drugs in patients with PH associated with left heart disease is currently observed at an increasing rate. This development is a matter of concern. On the other hand, PH is a frequent problem that is highly relevant for morbidity and mortality in patients with left heart disease. In that sense, the distinction between isolated post-capillary pulmonary hypertension (IpcPH) and combined post- and pre-capillary pulmonary hypertension (CpcPH) and their proper definition may be of particular relevance. The detailed results and recommendations of the working group on PH associated with left heart disease, which were last updated in the spring of 2018, are summarized in this article.